Synthesis of Hydroxyapatite Bioceramics (Ca10(PO4)6(OH)2) of the Waste Cow Bone Using Sol-Gel Method - Wardhani, Sri; Darjito, Darjito; Pinangsih, Arum Candra (Jurnal Ilmu Kimia Universitas Brawijaya, 2014)
Hydroxyapatite bioceramics have been synthesized from waste cow bone using sol-gel method . The purpose of this study was to determine the effect of concentration HCl for the precursor CaCl2 mass produced and volume of H3PO4 for the synthesized hydroxyapatite. The results of this study, the optimum HCl concentration of the precursor synthesis was 1 M and the optimum volume H3PO4 on the synthesis of hydroxyapatite was 25 mL. Hydroxyapatite characterized by XRD, XRF, FTIR, dan SEM-EDX. XRD showed the presence of 23 peaks that were similar to the peak on hydroxyapatite standard. The highest intensity of peak present at 2q 25.93068, 50.44543, 48.70093, dan 49.0851. XRF demonstrated that the hydroxyapatite main constituent were calcium 80.1 % and phosphorus 14.0 %. wave number  of FTIR at 567,03; 3402,20; dan 1635,5 cm-1 showed the presence of PO43-, OH, and CaO groups on the synthesized hydroxyapatite. SEM EDX indicated size of synthesized hydroxyapatite were 0,52 mm and ratio of Ca:P were 1.04. Key words: bioceramic, hydroxyapatite, precursors, sol-gel